2016
DOI: 10.1371/journal.pone.0163316
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spatial and Temporal Resolution of Cine Phase Contrast MRI on Wall Shear Stress and Oscillatory Shear Index Assessment

Abstract: IntroductionWall shear stress (WSS) and oscillatory shear index (OSI) are associated with atherosclerotic disease. Both parameters are derived from blood velocities, which can be measured with phase-contrast MRI (PC-MRI). Limitations in spatiotemporal resolution of PC-MRI are known to affect these measurements. Our aim was to investigate the effect of spatiotemporal resolution using a carotid artery phantom.MethodsA carotid artery phantom was connected to a flow set-up supplying pulsatile flow. MRI measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 29 publications
5
70
0
Order By: Relevance
“…This partially agrees with findings made by Cibis et al, 15 who reported on a dependence of OSI on temporal resolution. This partially agrees with findings made by Cibis et al, 15 who reported on a dependence of OSI on temporal resolution.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This partially agrees with findings made by Cibis et al, 15 who reported on a dependence of OSI on temporal resolution. This partially agrees with findings made by Cibis et al, 15 who reported on a dependence of OSI on temporal resolution.…”
Section: Discussionsupporting
confidence: 93%
“…The latter has already been studied in related works, 13,15,19 although the extent of uncertainties induced by acquisition parameters compared to those induced by imprecise wall tracking had not been reported yet. Equally, we evaluated the influence of spatiotemporal resolution and phase noise in synthetic datasets using the identical implementation to estimate shear stress parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 2DRF pulse durations of about 3.5 ms reduced the temporal resolution compared with conventional 1‐dimensional (1D) slab‐selective RF pulses (1DRF, such as SINC) . The temporal resolution is, however, critical for correct peak flow quantification . Furthermore, the reduced FOV (rFOV) needs to be oversampled in both phase‐encoding directions (i.e., rFOV > FOX), to prevent static spatial aliasing, which prolongs the scan time.…”
Section: Introductionmentioning
confidence: 99%